The finite-difference time-domain (FDTD) and the finite-volume time-domain (FVTD) methods in solving Maxwell's equations - Yee, K.S.; Chen, J.S. (IEEE transactions on antennas and propagation, 1997)
The finite-difference time-domain (FDTD) and its current generalizations have been demonstrated to be useful and powerful tools for the calculation of the radar cross section (RCS) of complicated objects, the radiation of antennas in the presence of other structures, and other applications. The mathematical techniques for conformal FDTD have matured; the primary impediments to its implementation are the complex geometries and material properties associated with the problem. Even under these circumstances, FDTD is more flexible to implement because it is based on first principles instead of a clever mathematical trick. This paper gives an account of some new results on conformal FDTD obtained by the authors and their associates at Lockheed Martin Space Company since 1988. The emphasis is on nonsmooth boundary condition simulation.